Application Of Criminal Sanctions To Perpetrators Of Crimes Intentionally And Without Rights Against The Law Accessing Computers Or Electronic Systems Other People's Own (Study of Tanjung Karang District Court Decision Number 596/Pid.Sus/2025/PN Tjk) - adik, Annafi Akbar; Anggalana (International Journal of Education, Vocational and Social Science, 2026)
One of the decisions related to the criminal act of intentionally and without the right to access another person's computer or electronic system is recorded in the Tanjung Karang District Court Decision Number 596/Pid.Sus/2025/PN Tjk. In this case, the Defendant VAR bin I is suspected of committing the act in the period April 2022 to December 2024 at his residence in Kupang Jernih, Sukarame II Village, West Teluk Betung District, Bandar Lampung City, or other locations that are still within the jurisdiction of the Tanjung Karang District Court. This study aims to analyze the application of criminal sanctions and the judge's considerations in imposing penalties on the perpetrator based on the decision. The research method uses a normative and empirical juridical approach with primary and secondary data, through library and field research, and is analyzed qualitatively. The results of the study indicate that the application of criminal sanctions against the defendant is based on Article 30 paragraph (1) in conjunction with Article 46 paragraph (1) of Law No. 1 of 2024 concerning the Second Amendment to Law No. 11 of 2008 concerning Electronic Information and Transactions and Law No. 8 of 1981 concerning Criminal Procedure Law, with a prison sentence of 9 months and a fine of Rp5,000,000,-, replaced by 3 months imprisonment if the fine is not paid. The judge's considerations include aggravating factors, namely unlawful acts, as well as mitigating factors, such as the defendant's confession, polite behavior, no previous convictions, and reconciliation with the victim. This reflects the judge's efforts to balance justice, deterrent effects, and mitigating circumstances for the defendant. It is recommended that law enforcement officers and judges always consider evidence, motives, and mitigating or aggravating circumstances to ensure a fair, proportional, and legal-compliant verdict.